KEARIFAN LOKAL MURO: BENTENG PELESTARIAN LAUT MASYARAKAT TAPOBARAN, LEMBATA - Maria Aprilia Meli Maing; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The Muro tradition is a manifestation of local wisdom in coastal management continuously practiced by the community of Tapobaran Village, Lembata Regency, East Nusa Tenggara. This practice is conducted through the temporary closure of specific marine areas to fishing activities based on a mutually agreed-upon customary consensus. The primary objective of this closure is to allow marine biological resources time to recover so they can develop naturally and sustainably. After the closure period concludes, the area is reopened through a customary ritual as a signal for the resumption of fishing activities. This study aims to describe the implementation stages of the Muro tradition, analyze its contribution to the balance of marine ecosystems and the improvement of the community’s economy, as well as identify the challenges in maintaining its sustainability. This research employs a qualitative approach with a descriptive method through in-depth interviews, field observations, and a review of related literature. The results indicate that the Muro tradition serves effectively as a community-based mechanism for regulating the utilization of marine resources. The temporary closure of fishing zones provides a positive impact in the form of increased marine biota populations and improved fish yields when the area is reopened. Nonetheless, the sustainability of this tradition faces obstacles, such as the intrusion of fishermen from outside the region who do not understand or comply with local customary rules, the current of globalization and modernization that is beginning to shift the perspective of the younger generation, and global climate change which renders marine conditions difficult to predict. Overall, the Muro tradition holds significant potential to be utilized as a reference in policy development.